Elevated Lipoprotein-Associated Phospholipase A2 Independently Affects Age-Related Increases in Systolic Blood Pressure: A Nested Case-Control Study in a Prospective Korean Cohort - Hye Jin Yoo; Minjoo Kim; Sang-Hyun Lee; Jong Ho Lee (International Journal of Hypertension)
Inflammatory markers are susceptible to changes over time. Thus, we observed changes in inflammatory markers correlating with age-related increases in blood pressure (BP) through a prospective study. The aim of this study was to investigate changes in inflammatory markers that correlate with age-related increases in BP. The study included 1,500 nondiabetic and normotensive healthy subjects at baseline. Of these, 121 individuals who developed hypertension (defined as systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg) after 2 years formed the hypertension group. For each incident hypertension case, 2 age- and sex-matched control subjects were selected among those who did not develop hypertension (control group, n = 242). After baseline adjustment, the hypertension group exhibited greater increases in body mass index (BMI), systolic and diastolic BP, triglyceride, total cholesterol, glucose, Lp-PLA2 activity, and urinary 8-epi-prostaglandin F2α (8-epi-PGF2α) levels compared to the control group. In the hypertension group, changes in (Δ) systolic BP correlated positively with Δ Lp-PLA2 activity, which correlated positively with Δ low-density lipoprotein (LDL−) cholesterol and Δ urinary 8-epi-PGF2α levels. Moreover, multiple linear regression revealed baseline systolic BP and Δ Lp-PLA2 activity to be independent predictors of Δ systolic BP in the hypertension group. Our results suggest that age-related increases in systolic BP may correlate strongly with elevated Lp-PLA2 activity and that Lp-PLA2 can be considered a biomarker for systolic BP elevation.